Obesity and COVID-19 Pandemics: Epidemiology, Mechanisms, and Management - Yang Y; Song Y; Hou D (Diabetes, Metabolic Syndrome and Obesity, 2023)
Yanping Yang,1 Yuanlin Song,1– 3 Dongni Hou2 1Shanghai Institute of Infectious Disease and Biosecurity, Fudan University, Shanghai, People’s Republic of China; 2Shanghai Key Laboratory of Lung Inflammation and Injury, Department of Pulmonary Medicine, Zhongshan Hospital, Fudan University, Shanghai, People’s Republic of China; 3Shanghai Respiratory Research Institute, Shanghai, People’s Republic of ChinaCorrespondence: Dongni Hou, Shanghai Key Laboratory of Lung Inflammation and Injury, Department of Pulmonary Medicine, Zhongshan Hospital, Fudan University, 180 Fenglin Road, Shanghai, People’s Republic of China, Email houdn2014@126.comAbstract: Obesity is a principle causative factor of various metabolic dysfunctions, chronic inflammation, and multi-organ impairment. The global epidemic of obesity has constituted the greatest threat to global health. Emerging evidence has associated obesity with an increased risk of severe infection and poor outcomes from coronavirus disease 2019 (COVID-19). During current COVID-19 pandemic, the interaction between COVID-19 and obesity has exaggerated the disease burden of obesity more than ever before. Thus, there is an urgent need for consideration of universal measures to reduce the risk of complications and severe illness from severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) in obesity population. In this review, we first summarized the clinical evidence on the effect of obesity on susceptibility, severity, and prognosis of COVID-19. Then we discussed and the underlying mechanisms, including respiratory pathophysiology of obesity, dysregulated inflammation, upregulated angiotensin-converting enzyme 2 (ACE2) expression, hyperglycemia, and adipokines. Finally, we proposed recommendations on how to reduce the spread and pandemic of SARS-CoV-2 infection by prevention and treatment of obesity.Keywords: obesity, COVID-19, metabolic syndrome, severe acute respiratory syndrome coronavirus 2, angiotensin-converting enzyme 2, inflammation